A Propensity-matched Survival Analysis: Do Simultaneous Liver-lung Transplant Recipients Need a Liver?. Issue 8 (August 2019) - Freischlag, Kyle; Ezekian, Brian; Schroder, Paul M.; Mulvihill, Michael S.; Cox, Morgan L.; Hartwig, Matthew G.; Knechtle, Stuart
Abstract : Background: There is debate whether simultaneous lung-liver transplant (LLT) long-term outcomes warrant allocation of 2 organs to a single recipient. We hypothesized that LLT recipients would have improved posttransplant survival compared with matched single-organ lung recipients with an equivalent degree of liver dysfunction. Methods: The Organ Procurement and Transplant Network/United Network for Organ Sharing STAR file was queried for adult candidates for LLT and isolated lung transplantation from 2006 to 2016. Waitlist mortality and transplant odds were calculated for all candidates. Donor and recipient demographic characteristics were compiled and compared. The LLT recipients were matched 1:2 with a nearest neighbor method to single-organ lung recipients. Kaplan-Meier methods with log-rank test compared long-term survival between groups. Univariate regression was used to calculate the association of LLT and mortality within 6 months of transplant. A proportional hazards model was used to calculate risk-adjusted mortality after 6 months posttransplantation. Results: Thirty-eight LLT patients were matched to 75 single-organ lung recipients. After matching, no differences in baseline demographics or liver function were observed between cohorts. Length of stay was significantly longer in LLT recipients compared to isolated lung recipients (45.89 days vs 22.44 days, P < 0.001). There was no significant difference in survival probability between LLT and isolated lung transplant (1 y, 89.5% vs 86.7%; 5 y, 67.0% vs 64.6%; P = 0.20). Conclusions: After matching for patient characteristics and level of liver dysfunction, survival in simultaneous LLT was comparable to isolated lung transplantation. Although this population is unique, the clinical picture prompting liver transplant is not clear. National guidelines to better elucidate patient selection are needed. Abstract : Supplemental Digital Content is available in the text.